Food & Business Global Challenges Programme GCP4 Midterm Workshop Report - CGIAR Research Program on Climate Change, Agriculture and Food Security; NWO-WOTRO Science for Global Development; Food & Business Knowledge Platform (2019)
This report summarizes the key highlights from the GCP4 Midterm Workshop and Public Dialogue on Scaling Climate-Smart Agriculture in East Africa held at the International Livestock Research Institute from June 12-14 2019, including a field trip held on June 15 2019. The workshop brought together 55 participants drawn from the eight GCP4 project teams, CCAFS, NWO and F&BKP. The public dialogue held on the afternoon of June 13 was attended by an additional 34 participants representing the private sector, research, non-governmental organizations, government and international development partners in Ethiopia. Finally, some of the participants visited the Iteya Agricultural Office and Kulumsa Agricultural Research Center on June 15 to learn about extension services, research and practice from rural agricultural centers in Ethiopia.